The cost function Φ(x, w) versus the number of iterations for different Gaussian noise levels: (a) σ = 10−2 and (b) σ = 10−3. - Limin Ma (556873) (2024)
The cost function Φ(x, w) versus the number of iterations for different Gaussian noise levels: (a) σ = 10−2 and (b) σ = 10−3.